2006
DOI: 10.1111/j.1365-2133.1994.tb08498.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphoea lesions are associated with aberrant expression of membrane cofactor protein and decay accelerating factor in vascular endothelium

Abstract: Summary One of the main features of systemic and localized forms of scleroderma is vascular damage, the mechanism of which is not yet understood. Recently, we have shown undetectable or decreased expression of complement regulatory molecules, membrane cofactor protein (MCP) and decay‐accelerating factor (DAF), in cutaneous endothelium of patients with systemic sclerosis (SSc). In some patients. CD59 expression in endothelium was also altered. As these molecules protect endothelial cells from damage by autologo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In patients with systemic sclerosis (Scleroderma or SSc), DAF was found to be decreased or undetectable in endothelium of both lesional skin and nonlesional skin compared to controls [37]. Interestingly this result was later reproduced in morphea lesions, suggesting a link between systemic autoimmune disease skin lesions and low DAF levels, although low DAF levels are also seen in psoriatic skin lesions [38, 39]. These studies, however, are limited by their power and lack of supporting follow-up studies.…”
Section: Daf In Human Autoimmune Diseasesmentioning
confidence: 99%
“…In patients with systemic sclerosis (Scleroderma or SSc), DAF was found to be decreased or undetectable in endothelium of both lesional skin and nonlesional skin compared to controls [37]. Interestingly this result was later reproduced in morphea lesions, suggesting a link between systemic autoimmune disease skin lesions and low DAF levels, although low DAF levels are also seen in psoriatic skin lesions [38, 39]. These studies, however, are limited by their power and lack of supporting follow-up studies.…”
Section: Daf In Human Autoimmune Diseasesmentioning
confidence: 99%
“…Moreover, they compared these samples with samples of HC and patients with other autoimmune diseases. MCP and DAF expression were altered only in SSc patients, suggesting defective endothelial protection, due to a reduced expression of complement regulatory proteins [29,30]. These results were confirmed by Scambi et al which detected the abnormal deposition of the membrane attack complex (MAC) on the endothelium in skin biopsies of SSc patients and reduced MCP expression on the vascular endothelial surface of patients.…”
Section: Discussionmentioning
confidence: 76%
“…The group of membrane-bound complement regulators include the membrane cofactor protein (MCP or CD46), which is a cofactor of FI in the proteolytic inactivation of C3b and C4b, and the decay accelerating factor (DAF or CD55), which accelerates the breakdown of C3- and C5-convertases [ 24 26 ]. Recently, Venneker et al demonstrated an impaired expression of MCP and DAF in endothelium of the lesional and non-lesional skin of SSc patients and in the skin of patients with morphea, in comparison to healthy controls and subjects affected by other autoimmune diseases, suggesting that a defective endothelial protection might be mediated by reduced expression of the complement regulatory proteins [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%